Infectivity analysis of Ageratum yellow vein virus-Malaysia isolate and its associated dna betasatellite component in Solanum lycopersicum / Mazni Omar - Mazni , Omar (2019)

(untitled)
The previous study has shown that the virus isolated from infected tomato leaves in peninsular Malaysia, showing leaf curl disease symptoms is a monopartite whitefly-transmitted Begomovirus from Geminiviridae family. The virus isolate was identified with a single-stranded DNA-A like genome and its associated DNA betasatellite. Despite the finding on these viral DNAs, no detail study has been down to investigate the effect of the betasatellite on the helper virus. Therefore, in this study, infectivity analysis was conducted using newly constructed agroinfectious clones harboring individual amplified viral DNAs, in the binary vector pCAMBIA1304. The susceptible tomato plants (Solanum lycopersicum) were either co-inoculated with both virus and betasatellite or single inoculated with only the virus. Our results showed both developed agroinfectious clones were infectious and could produce the leaf curl symptoms in the inoculated S. lycopersicum. However, the co-inoculation with betasatellite caused more severe leaf curl phenotypes, slower growth rate, shorter latent period and higher virus accumulation in the symptomatic co-inoculated plants as compared to single inoculated plants without betasatellite. This study marks significant findings on the fundamental knowledge of the begomovirus-betasatellite complex in S. lycopersicum as well as an important milestone towards future improvements on effective RNAi-mediated defense strategy against this virus.